2007
DOI: 10.4028/www.scientific.net/amr.20-21.50
|View full text |Cite
|
Sign up to set email alerts
|

Mobilization of Silver, Gold, and Platinum from Solid Materials by HCN-Forming Microorganisms

Abstract: Cyanogenic Chromobacterium violaceum, Pseudomonas fluorescens, and P. plecoglossicida were able to mobilize silver, gold and platinum when grown in the presence of various metal-containing solids such as powdered platinum, platinum-containing automobile catalytic converters, powdered silver, or gold-containing electronic scrap. Five percent of silver was mobilized from powdered jewelry scrap as dicyanoargentate after one day, although 96% was mobilized when non-biological cyanide leaching was applied. Dicyanoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…As such, strain 2002 could not mobilize metals via the formation of metal-cyanide complexes, in a similar manner to C. violaceum (Brandl et al 2007;Reith et al 2007). However, the ability of strain 2002 to directly oxidize metals can directly influence metal mobility in the environment (Chaudhuri et al 2001;Cornell & Schwertmann 2003;Lack et al 2002b;Weber et al 2001;Weber et al 2006c).…”
Section: Hydrolysis Of Gelatinmentioning
confidence: 92%
See 1 more Smart Citation
“…As such, strain 2002 could not mobilize metals via the formation of metal-cyanide complexes, in a similar manner to C. violaceum (Brandl et al 2007;Reith et al 2007). However, the ability of strain 2002 to directly oxidize metals can directly influence metal mobility in the environment (Chaudhuri et al 2001;Cornell & Schwertmann 2003;Lack et al 2002b;Weber et al 2001;Weber et al 2006c).…”
Section: Hydrolysis Of Gelatinmentioning
confidence: 92%
“…The metabolic versatility of Chromobacterium spp., specifically C. violaceum, has resulted in a variety of industrial applications (Vasconcelos et al 2003). Related to metal biogeochemistry, the biogenic production of cyanide during aerobic growth of C. violaceum has been demonstrated to mobilize precious metals such as silver, gold, and platinum as a result of the formation of metal-cyanide aqueous complexes (Brandl et al 2007;Reith et al 2007). The ability of this microorganism to oxidize aqueous Fe(II) to an insoluble Fe(III) oxide mineral under anaerobic conditions at neutral pH in addition to strain 2002 was recently demonstrated (Weber et al 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…These results show that pH tends to decrease for the entire duration of the experiment, although this drop becomes more significant at the 4th day. In maximum growth at day 5, a dramatic decrease in the DO level was seen, indicating more oxygen consumption by increased growth . Thereafter, DO increased, pH variation was minimal, and OD 600 decreased implying that bacterial activity was diminished, and wastes had accumulated.…”
Section: Resultsmentioning
confidence: 99%
“…In maximum growth at day 5, a dramatic decrease in the DO level was seen, indicating more oxygen consumption by increased growth. 27 Thereafter, DO increased, pH variation was minimal, and OD 600 decreased implying that bacterial activity was diminished, and wastes had accumulated. It is concluded that holding the pH level over the bacterial growth period can significantly limit and delay the activity.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%